Az Egyesítő Egyház - Török Péter (Vallás a társadalomban = Religion in society, 2008)
The aim of this study is to get to know the history, teachings, Hungarian presence and social appreciation of the Unification Church. Beside the review of the available Hungarian and foreign sources, the highest possible objectivity is achieved by discussions with the representatives of the Unification Church, and participant observation. Though I am aware of the risks of such a task, I try to make some statements in the conclusion of this study, which compares the true state of this community with the image they have in the Hungarian society.